Maleimide-functionalized poly(2-ethyl-2-oxazoline): synthesis and reactivity. Issue 13 (14th March 2016) - Wendler, Felix; Rudolph, Tobias; Görls, Helmar; Jasinski, Nils; Trouillet, Vanessa; Barner-Kowollik, Christopher; Schacher, Felix H.
Abstract : Poly(2-ethyl-2-oxazoline)s end-functionalized with a maleimide moiety were prepared from azide-terminated PEtOx x -N3 via copper-catalyzed azide–alkyne cycloaddition (CuAAC) with an alkyne-bearing maleimide (MI). Abstract : Poly(2-ethyl-2-oxazoline)s (PEtOx23 – M n = 2300 g mol −1, Đ = 1.07; PEtOx46 – M n = 4400 g mol −1, Đ = 1.06) end-functionalized with a maleimide moiety were prepared from azide-terminated PEtOx x -N3 via copper-catalyzed azide–alkyne cycloaddition (CuAAC) with an alkyne-bearing maleimide (MI). The latter has been synthesized in a three-step procedure, including protection of the maleimide double bond prior to the modification of PEtOx. PEtOx x -MI was characterized by NMR ( 1 H, 13 C), SEC, FT-IR, and MALDI-ToF MS and, after deprotection of the maleimide, used in nitrile imine-mediated tetrazole-ene cycloaddition (NITEC) processes for covalent attachment to silicon surfaces in a grafting-to approach.